Mechanical thrombectomy using the retrograde semi-retrieval technique for patients with underlying intracranial atherosclerotic stenosis - Wang, Wei; Xu, Yongbo; Zhang, Bohao; Liu, Shuling; Ma, Zhenjian; Wang, Sifei; Zhang, Pinyuan; Wei, Ming (Frontiers in Neurology, 2024)
Background The retrograde semi-retrieval technique (RESET) has been described as a modified technique for endovascular thrombectomy (EVT) whose safety and efficacy for intracranial atherosclerosis stenosis (ICAS) patients remain uncertain. This article presents our single-center experience, comparing RESET vs. non-RESET in ICAS patients. Materials and methods We analyzed 327 consecutive ICAS patients who underwent EVT at Tianjin Huanhu Hospital from January 2018 and December 2022. Patients were categorized into two groups: RESET and non-RESET. The primary outcome was the first-pass effect (FPE). Secondary outcomes included successful reperfusion, functional independence at 90 days, mortality, and symptomatic intracranial hemorrhage (sICH). Results RESET was significantly associated with FPE [adjusted odds ratio (aOR) 2.00, 95% confidence interval (CI) 1.03–3.87, p = 0.040]. RESET was not significantly associated with successful reperfusion (aOR 1.5, CI 0.55–4.06, p = 0.425), an mRS of 0–2 at 90 days (aOR 1.36, CI 0.83–2.21, p = 0.223), sICH (aOR 0.39, CI 0.12–1.23, p = 0.108), and mortality (aOR 0.49, CI 0.16–1.44, p = 0.193). After propensity score matching, the results were consistent with the primary analysis. Conclusion Compared to non-RESET, patients treated with RESET showed increased FPE incidence and significantly decreased puncture-to-reperfusion time. RESET was proven to be safe and effective in enhancing reperfusion for LVO patients receiving EVT with underlying ICAS.